Update on the classification of myeloid neoplasms: The 2016 revised World Health Organization classification of hematopoietic and lymphoid neoplasms. Issue 2 (6th December 2019) - Sangiorgio, Valentina; Orazi, Attilio
Abstract: In recent years, a large body of knowledge regarding the molecular genetics of myeloid malignancies has emerged and molecular findings have become increasingly important not only for diagnosis but also to establish prognosis and treatment of patients with myeloid malignancies. Clinical and pathological findings have been refined in relation to their diagnostic/prognostic value. The integration of all these different parameters represents the backbone of the 2016 revised 4th Edition of the WHO Classification of Tumours of Hematopoietic and Lymphoid Tissues. The current review aims to highlight the main changes between the 2008 WHO Classification and the most recent 2016 revised 4th edition, with regard to the classification of myeloid malignancies.